ROLE OF WORK DISCIPLINE, TEAM COOPERATION, AND COMPENSATION IN SHAPING EMPLOYEE PERFORMANCE AT PT. SUMATERA PRIMA FIBREBOARD - Arsita, Resi; Juhaini Alie (Jurnal Ilmu Manajemen (JIMMU), 2025)
This study investigates the impact of work discipline, teamwork, and compensation on employee performance at PT Sumatera Prima Fibreboard. Preliminary observations and interviews revealed that a lack of work discipline, poor teamwork, and dissatisfaction with compensation were hindering employee performance and the achievement of organizational goals. This research addresses these issues by examining the direct effects of these three variables. A quantitative approach was employed, with data collected through structured questionnaires distributed to 204 employees, a sample determined using Slovin's formula with a 5% margin of error from a total population of 416. Data analysis was conducted using SPSS version 30, utilizing multiple linear regression and partial t-tests at a 5% significance level. The results consistently demonstrated that work discipline, teamwork, and compensation each had a positive and significant effect on employee performance. These findings align with existing theories in human resource management regarding performance enhancement. While limited by its cross-sectional design, this study offers novelty by simultaneously examining these key variables within the underexplored context of the wood processing industry in Palembang. Practically, the findings provide valuable guidance for managerial decision-making, enabling the formulation of policies that prioritize employee development through reinforced discipline, fostering collaborative synergy, and implementing fair compensation systems